2022
DOI: 10.1002/lio2.762
|View full text |Cite
|
Sign up to set email alerts
|

Management of clinically node‐negative glottic squamous cell carcinoma patients according to risk‐scoring model for occult lymph node metastases

Abstract: Background Glottic squamous cell carcinoma (GSCC) is the most prevalent type of laryngeal carcinoma. The value of prophylactic lymph node dissection (LND) in resected GSCC remains controversial. This study aims to quantitatively assess the probability of occult lymph node metastasis (LNM) for GSCC patients and devise individualized postoperative radiotherapy strategies. Methods A total of 1319 patients with GSCC were retrospectively analyzed. Results GSCC patients with T1‐T2 stages showed significantly lower L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…The accuracy, precision, recall rate, F1-score, AUC value, specificity, and calibration plots were performed to evaluate and compare the ML model performances, and we found that XGBoost was better than the other models with respect to the AUC value, Brier score, F1-score, recall rate, and accuracy, whether it was in the training set or in the test set ( Table 4 , Figures 4(a) , 4(b) , 5(a), and 5(b)). In addition, the AUC value of XGBoost was also higher than that of the model constructed in previous studies [ 8 , 34 , 37 ]. Therefore, we believe that XGBoost was the best predictive model to predict the LNM in LC patients.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The accuracy, precision, recall rate, F1-score, AUC value, specificity, and calibration plots were performed to evaluate and compare the ML model performances, and we found that XGBoost was better than the other models with respect to the AUC value, Brier score, F1-score, recall rate, and accuracy, whether it was in the training set or in the test set ( Table 4 , Figures 4(a) , 4(b) , 5(a), and 5(b)). In addition, the AUC value of XGBoost was also higher than that of the model constructed in previous studies [ 8 , 34 , 37 ]. Therefore, we believe that XGBoost was the best predictive model to predict the LNM in LC patients.…”
Section: Discussioncontrasting
confidence: 56%
“…However, due to the complexity and large size of the various factors in the data and the differences among the calculation methods of the models, the prediction performance was also significantly different. Heng et al [ 37 ] developed a nomogram to predict the occult lymph node metastases of glottic squamous cells with an AUC value of 0.716. Chen et al [ 34 ] used a nomogram to predict cervical LNM in laryngeal squamous cell carcinoma with an AUC value of 0.809.…”
Section: Discussionmentioning
confidence: 99%
“…The laryngeal subsites (supraglottis, glottis, and subglottis) show marked differences in terms of the risk of lymph node metastasis 6,7 . Malignant tumors of supraglottic origin have a greater tendency for locoregional involvement; the percentage of lymph node metastases identified in exclusively glottic or subglottic carcinomas is less pronounced 8,9 . The subsite of origin of the tumor is one of the factors that determine the behavior of laryngeal neoplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies 13,14 have defined the preferential patterns of lymph node metastasis. Laryngeal squamous cell carcinomas tend to affect levels I and V at very low percentages, and in almost all cases, there is simultaneous involvement of levels II–IV 9 . Tumors arising in the median supraglottic region and advanced‐stage tumors of the glottic region (T3‐T4) preferentially metastasize to levels II–III and IV, frequently bilaterally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation